Wine all-in-one for dummies - McCarthy, Ed. (Hoboken, N.J. : Wiley, 2009)
Discusses wine vintages and provides advice on how to sample various types of wines, how to judge wine by its label, the art of selecting the right wine, how to serve and store wine, and how to distinguish good wine from bad, along with information on prominent wine-making countries.
Includes index.
Keywords: Wine and wine making; Wine and wine making